Using Personal Branding Method to Improves Reproductive Health Knowledge among Youth Orphanage - Made Dwi Adnjani; Noveri Aisyaroh; Isna Hudaya (Universitas Muhammadiyah Surakarta, 2021)
The large population of the adolescent group in Indonesia must be guaranteed to grow and develop positively and free from various problems including reproductive health problems. At this period, adolescents experience many challenges both from themselves and surrounding environment, therefore they need to have the ability to address these issues. Partner in this program is the The Noor Hidayah Orphanage, with the number of 35 adolescents. Health problems among those teenage children are lack of nutritional needs completed with signs of anemia, lack of Clean and Healthy Behavior (CHB), less of self-confidence and feel insecure about their conditions. The proposed intervention based on partner problems, namely improving reproductive health status and branding skill for adolescents. In particular, providing counseling about health reproductive, nutrition for adolescents, FGD on CHB, Hb examination for early detection of anemia and the establishment of adolescent health care services. Improving self-branding skills was conducted by providing counseling on the importance of personal branding for a public figure as well as providing training to build personal branding through public speaking skills. At the end of the program, it revealed that around 41.9% teenage had mild anemia, improved knowledge of reproductive health and CHB, the formation of health cadres and they were more confident in seeing themselves and their lives in the future.